Correlative full field X-ray compton scattering imaging and X-ray computed tomography for in situ observation of Li ion batteries. (January 2023) - Leung, Chu Lun Alex; Wilson, Matthew D.; Connolley, Thomas; Collins, Stephen P.; Magdysyuk, Oxana V.; Boone, Matthieu N.; Suzuki, Kosuke; Veale, Matthew C.; Liotti, Enzo; Van Assche, Frederic; Lui, Andrew; Huang, Chun
Abstract: Increasing electrode thickness is gaining more attention as a potential route to increase energy density for Li ion batteries although the realizable capacity and rate capability are usually limited by Li + ion diffusion during (dis)charge, especially at increased (dis)charge rates. It remains challenging to visualize and quantify the low atomic number Li + chemical stoichiometry distribution inside the electrode within commercially standard battery geometry, e.g. coin cells with stainless steel casings. Here, we map the distribution of Li  +  chemical stoichiometry in the electrode microstructure inside a working coin cell battery to show the amount of electrode materials contributing to energy storage performance using innovative in situ correlative full-field X-ray Compton scattering imaging (XCS-I) and X-ray computed tomography (XCT). We design and fabricate an ultra-thick (∼1 mm) cathode of LiNi0.8 Mn0.1 Co0.1 O2 with a microstructure containing vertically oriented pore arrays using a directional ice templating method. This novel technique paves a new way to map low atomic number elements in 3D structures and study how the microstructure improves Li  +  ion diffusivity and energy storage performance. Graphical abstract: Image 1 Highlights: In situ correlative imaging to study structure/electrochemical properties relationship. First full-field XCS-I of obtaining spectra across the battery plane simultaneously. Results show heterogeneity in lateral distribution of Li + in the battery electrode. Directional ice templating to make thick electrodes with anisotropic microstructure.